Covid-19 Theme English Module Development - Rahmadhani Rambe, Kartina; Reza Pahlevi, Muhammad; Panjaitan, Efrini (Green Publisher Indonesia, 2022)
Study this aim for produce module language English COVID-19 themed aimed at to students of the four -oriented Elementary School Teacher Education study program competence base that is listen, speak, read and write. Method applied research is Research Development (R and D) with Rowntree model consisting of on stages planning, development and evaluation. In phase evaluation, use the evaluation model formative Tessmer with stages of self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Evaluation results Step self-evaluation that is conducted several revisions module for tested level validation by the validator team. At the expert review stage it is generated module valid category with average validation content 0.82, format validation 0.84, and validation serving 0.84. In the one to one evaluation stage with 3 students as sample, result questionnaire response third student the to developed module categorized practical. In the small group evaluation stage with 9 students as sample, result analysis questionnaire response student to module that module describe level practicality as teaching materials with an average of 82.3%. Based on results stages evaluation could declared that developed module has tested practicality so that could made as one of the learning media